Photophysical investigation of charge recombination in CdS/ZnO layers of CuIn(S,Se)2 solar cell - Nalla, Venkatram (2014)
Excitation wavelength dependent femtosecond transient photocurrents were measured on CuIn(S,Se) 2 solar cell devices, in the range of 330 nm–1300 nm. Below 450 nm wavelength excitations, charge recombination in CdS/ZnO layers is found to be responsible for longer decays and lower EQE. Femtosecond pump-probe measurements also support the charge transfer and recombination in CdS/ZnO layers. These measurements will be helpful to design high efficiency CISSe solar cells, by selecting suitable buffer layers.